Affirmative Action and Intersectionality at the Top: Evidence from South Africa - Stephan Klasen; Anna Minasyan (Global Labor Organization (GLO), 2020)
Gender-based board quotas do not always lead to higher share of women in top management positions. We study the consequences of an affirmative action policy that stipulates gender- and race-based targets in top management positions, beyond boards. We focus on the representation of intersectional group identities, such as race and gender, at the top. We find sizable increase in the likelihood of Black women employment in top positions in the post-policy period relative to Black men, White women and White men in South Africa. We extend our analysis and estimate policy spillovers for years of schooling, earnings gaps and self-employment.
Keywords: H41; J18; J21; J71; K31; 330; affirmative action; top; employment; race; gender; South Africa